2011
DOI: 10.1017/s1446788711001303
|View full text |Cite
|
Sign up to set email alerts
|

Invariant Einstein Metrics on Generalized Flag Manifolds With Two Isotropy Summands

Abstract: Let M = G/K be a generalized flag manifold, that is, an adjoint orbit of a compact, connected and semisimple Lie group G. We use a variational approach to find non-Kähler homogeneous Einstein metrics for flag manifolds with two isotropy summands. We also determine the nature of these Einstein metrics as critical points of the scalar curvature functional under fixed volume.2010 Mathematics subject classification: primary 53C25; secondary 53C30, 22E46.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 18 publications
1
56
0
5
Order By: Relevance
“…Then, it is evident that m = m 2 ⊕ m 4 , and m is a linear subspace of m = ⊕ 4 k=1 m k . In [8], it was shown that (c 4 22 4 , so by using Table 5, we obtain the following values: …”
Section: Proposition 8 Let M = G/k Be a Generalized Flag Manifold Of mentioning
confidence: 92%
See 2 more Smart Citations
“…Then, it is evident that m = m 2 ⊕ m 4 , and m is a linear subspace of m = ⊕ 4 k=1 m k . In [8], it was shown that (c 4 22 4 , so by using Table 5, we obtain the following values: …”
Section: Proposition 8 Let M = G/k Be a Generalized Flag Manifold Of mentioning
confidence: 92%
“…In our case, the fibers U /K are the spaces SO (9) (10), and E 7 /SU (7) × U (1), respectively. These are generalized flag manifolds with two isotropy summands (see [8]), so we can easily compute the triples (c 4 22 ) for the spaces U /K . Let B G = B and B U denote the Killing forms of G and U , respectively, and let u = k ⊕m be a reductive decomposition of u with respect to B U , where m ∼ = T eK (U /K ).…”
Section: Proposition 8 Let M = G/k Be a Generalized Flag Manifold Of mentioning
confidence: 99%
See 1 more Smart Citation
“…According to [2] and [3], a generalized flag manifolds has two isotropy summands if, and only if, Π K = Π − {α i0 } such that the simple root has Table 1. Generalized flag manifolds with two isotropy summands…”
Section: Theorem C Consider the Generalized Flag Manifoldmentioning
confidence: 99%
“…In particular all vectors in these subspaces are structural equigeodesic vectors. 3 , α 4 α 5 , α 6 } be a system of simple roots for E 6 such that the highest root is given by μ = α 1 + 2α 2 + 2α 3 +3α 4 +2α 5 +α 6 . The flag manifold E 6 /SU (5)×SU (2)×U (1) is determined by Π K = Π − {α 5 }.…”
Section: Flags Of Exceptional Lie Groupsmentioning
confidence: 99%